Determinants and heterogeneity of switching costs in IT outsourcing: estimates from firm-level data. Issue 3 (4th May 2019) - Peukert, Christian
ABSTRACT: We study how firms decide whether to continue an existing relationship or switch the vendor of outsourced services. Because of incomplete contracts and relationship-specific investments, client organisations may face switching costs, which in some cases may be large enough to render vendor switching an unattractive option. Based on an extensive review of the literature, we develop hypotheses about relationship-, firm-, and market-specific determinants of switching costs. We then develop an econometric model to identify those determinants and their relative importance and estimate the magnitude of switching costs. In the empirical study, we observe accounting data of 1318 US credit unions (CUs) and follow their IT outsourcing choices over 11 years. We find that the largest portion of switching costs is due to relationship- and firm-specific factors, while market-specific variables are much less important. Our estimates suggest that average switching costs account for one-third of the average annual expenditure for professional services. We further highlight that the average hides substantial heterogeneity. Switching costs of CUs that decide to switch vendors are about 50% lower than those of CUs that stay. Looking more closely at stayers, our most conservative estimate of the lock-in effect, i.e., the difference in switching costs of deliberate and non-deliberate stayers, is equivalent to about 70% of the average annual expenditure for professional services.